2023
DOI: 10.1111/myc.13653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic factors affecting trough levels of isavuconazole in critically ill patients with or without COVID‐19

Ralph Bertram,
Hans‐Theodor Naumann,
Vanessa Bartsch
et al.

Abstract: BackgroundThe broad‐spectrum antifungal isavuconazole is administered to treat invasive aspergillosis and mucormycosis.ObjectivesIsavuconazole plasma concentrations in critically ill ICU patients with or without COVID‐19 and invasive fungal infection were determined, and factors for sub‐therapeutic drug levels (<1 μg/mL) were evaluated.Patients and MethodsIsavuconazole plasma levels were measured as part of therapeutic drug monitoring (TDM) in ICUs of a tertiary hospital. Concentrations determined 20–28 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In 2 recently published cases, the 24-hour areas under the concentration–time curve and trough concentrations of isavuconazole were lower in both patients with ECMO in comparison with previously published data from non-ECMO patients [ 26 ]. Another case series including 9 critically ill patients with IFD and ECMO revealed that isavuconazole plasma levels were lower in patients receiving ECMO therapy compared with patients without ECMO [ 27 ]. A recent study included 18 critically ill patients, of whom 5 had CAPA, ECMO, and isavuconazole treatment.…”
Section: Antifungal Agentsmentioning
confidence: 99%
“…In 2 recently published cases, the 24-hour areas under the concentration–time curve and trough concentrations of isavuconazole were lower in both patients with ECMO in comparison with previously published data from non-ECMO patients [ 26 ]. Another case series including 9 critically ill patients with IFD and ECMO revealed that isavuconazole plasma levels were lower in patients receiving ECMO therapy compared with patients without ECMO [ 27 ]. A recent study included 18 critically ill patients, of whom 5 had CAPA, ECMO, and isavuconazole treatment.…”
Section: Antifungal Agentsmentioning
confidence: 99%